Ammonium-nitrogen removal from synthetic wastewater by electrodialysis - Pingul-Ong, Sheila Mae B.
The efficiency of a tailor-made electrodialysis unit in removing ammonium from synthetic wastewater was evaluated in a laboratory scale re-circulating batch process. Two graphical methods were used to determine the limiting current density at varying concentrations of 400, 800 and 1600 ppm NH₄-N, both of which determined that the relationship between current and voltage fell in the Ohmic region up to the maximum voltage of 30 V. Parametric experiments were performed, at varying control factors, namely, applied voltage of 10, 20 and 30 V, feed flow rates of 3, 4 and 5 LP, initial feed concentrations of 400, 800 and 1600 ppm, initial concentrations of 5%, 10%, 20%, 50% and 100% of the feed concentration, frequency of polarity reversal every 0, 15 and 30 min, and electrolyte solutions of NH₄NO₃, NH₄Cl and (NH₄)₂SO₄. Results showed that % NH₄-N removal was directly proportional to applied voltage, feed flow rate, initial feed concentration, and frequency of polarity reversal, but was inversely proportional to initial concentration of the concentrate tank and valence of the ionic species. Optimization experiments were done using Taguchi L₉ ortogonal array. Delta values showed that operating time had the greatest effect on NH₄-N removal, followed by initial feed concentration, applied voltage and feed flow rate. Graphical examination revealed that main effects were present for initial feed concentration, applied voltage and operating time, all of which proved to be statistically by ANOVA. The model equation was generated to depict the contributions of the control factors in % removal of NH₄-N had an average of 0.87% error between actual and predicted values. Optimum condition for a maximum of 45.02% NH₄-N removal was determined at 1,599.98 ppm initial feed concentration, 30 V applied voltage, 5 LPM feed flow rate, and 30.34 minutes of operating time.